Do children evaluated for maltreatment have higher subsequent emergency department and inpatient care utilization compared to a general pediatric sample?. (December 2022) - Liu, Yuerong; Shepherd-Banigan, Megan; Evans, Kelly E.; Stilwell, Laura; Terrell, Lindsay; Hurst, Jillian H.; Gifford, Elizabeth J.
Abstract: Background: Child maltreatment leads to substantial adverse health outcomes, but little is known about acute health care utilization patterns after children are evaluated for a concern of maltreatment at a child abuse and neglect medical evaluation clinic. Objective: To quantify the association of having a child maltreatment evaluation with subsequent acute health care utilization among children from birth to age three. Participants and setting: Children who received a maltreatment evaluation (N = 367) at a child abuse and neglect subspecialty clinic in an academic health system in the United States and the general pediatric population (N = 21, 231). Methods: We conducted a retrospective cohort study that compared acute health care utilization over 18 months between the two samples using data from electronic health records. Outcomes were time to first emergency department (ED) visit or inpatient hospitalization, maltreatment-related ED use or inpatient hospitalization, and ED use or inpatient hospitalization for ambulatory care sensitive conditions (ACSCs). Multilevel survival analyses were performed. Results: Children who received a maltreatment evaluation had an increased hazard for a subsequent ED visit or inpatient hospitalization (hazard ratio [HR]: 1.3, 95 % confidence interval [CI]: 1.1, 1.5) and a maltreatment-related visit (HR: 4.4, 95 % CI: 2.3, 8.2) relative to the general pediatric population. A maltreatment evaluation was not associated with a higher hazard of health care use for ACSCs (HR: 1.0, 95 % CI: 0.7, 1.3). Conclusion: This work can inform targeted anticipatory guidance to aid high-risk families in preventing future harm or minimizing complications from previous maltreatment.